Design and construction of a 25 kg plastic waste incinerator - Suharyanto; Fauzi Ashari; Fala Putrama; Abimanyu Awang Putra Nugroho (Politeknik ATK Yogyakarta, 2025)
The management of non-recyclable plastic waste in various Waste Banks and 3R Waste Transfer Stations (TPS 3R) in the Sleman Regency serves as the background for the development of this waste processing incinerator. This research aims to design and construct an incinerator prototype as a waste processing tool suitable for application at Waste Banks or TPS 3R facilities. The results are expected to provide crucial insights for improving combustion efficiency and reducing exhaust emissions, thereby making the plastic waste combustion process more environmentally friendly and efficient. The designed waste processing capacity has a volume of 1 m³, equipped with a wet scrubber to eliminate exhaust pollutants before release into the atmosphere. The incinerator dimensions are designed to measure 900 mm x 900 mm x 1000 mm. Combustion test results indicated a duration of 30 minutes for the waste to burn thoroughly and turn into ash. From an initial 25 kg of waste, the remaining mass after combustion was 4.05 kg. The design and construction of the incinerator required a budget of Rp 37,373,200.00. This plastic waste incinerator design is expected to serve as a waste processing solution for both TPS 3R facilities and Waste Banks.